Regional invasion history and land use shape the prevalence of non‐native species in local assemblages - Liu, Daijun (2024)
The ecological impact of non-native species arises from their establishment in local assemblages. However, the rates of non-native spread in new regions and their determinants have not been comprehensively studied. Here, we combined global databases documenting the occurrence of non-native species and residence of non-native birds, mammals, and vascular plants at regional and local scales to describe how the likelihood of non-native occurrence and their proportion in local assemblages relate with their residence time and levels of human usage in different ecosystems. Our findings reveal that local non-native occurrence generally increases with residence time. Colonization is most rapid in croplands and urban areas, while it is slower and variable in natural or semi-natural ecosystems. Notably, non-native occurrence continues to rise even 200 years after introduction, especially for birds and vascular plants, and in other land-use types rather than croplands and urban areas. The impact of residence time on non-native proportions is significant only for mammals. We conclude that the continental exchange of biotas requires considerable time for effects to manifest at the local scale across taxa and land-use types. The unpredictability of future impacts, implied by the slow spread of non-native species, strengthens the call for stronger regulations on the exchange of non-native species to reduce the long-lasting invasion debt looming on ecosystems' future.